HUBUNGAN MOTIVASI BELAJAR DENGAN PERILAKU BELAJAR MAHASISWA STAI BUMI SILAMPARI LUBUKLINGGAU - Wati Ningsih (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2017)
Motivation to learn is a motivation that sagat useful in supporting the success, this motivation comes from within yourself and not from outside factors in the form of encouragement of others. Learning behavior can also be associated with learning activities are also closely related to the habits or learning activities is all the activities of learners in the learning process from physical activity to physical activity, physical activities in the form of basic skills while the physical activity in the form of integrated skills. This research is a quantitative research by taking samples of 153 students. Methods of data collection in this study using questionnaires, documentation, and observation. The results of research that researchers get that the motivation to study STAI Bumi Silampari Lubuklinggau students are in the category